A study of the application of automatic healthcare tracking and monitoring system in Saudi Arabia. Issue 2 (27th May 2014) - Alharbe, Nawaf; S. Atkins, Anthony
Abstract : Purpose: – This paper aims to outline the results of a study of the potential use of sensor technology such as radio frequency identification (RFID) and/or ZigBee technology in providing real-time tracking and tracing of patients and equipment in hospitals. The government of Saudi Arabia has given high priority to providing the best practice in patients' care. However, the growing requirement of the healthcare industry to obtain real-time information and data from various applications that can improve the performance and accuracy of management systems has not been addressed seriously in Saudi Arabia. Design/methodology/approach: – ZigBee and RFID are both emerging technologies and have become important topics in recent years. RFID technology is a non-contact identification technology that does not require direct eyesight to the target object. It is cheap and reliable, but its coverage zone is limited. ZigBee is another communication technology, which has a larger coverage and can also be used as an automatic identification technology with the benefits of lower power consumption. Findings: – This paper proposes a smart hospital management system that can be used to detect, locate and monitor patients and track assets and equipment using modern sensor technologies in a real-time environment for e-health systems in Saudi Arabia. Originality/value: – A novel management information system/knowledge management system framework based on sensor technologies for supporting and speeding up development of healthcare systems.